Handbook of troubleshooting plastics processes : a practical guide - Wagner, John R. (Hoboken, New Jersey : John Wiley & Sons, Inc., 2012)
'This handbook provides a framework for understanding how to characterize plastic manufacturing processes for use in troubleshooting problems. The 21 chapters are authored by well-known and experienced engineers who have specialized knowledge about the processes covered in this practical guide.From the Preface:'In every chapter, the process is described and the most common problems are discussed along with the root causes and potential technical solutions. Numerous case studies are provided that illustrate the troubleshooting process. Mark A. Spalding, The Dow Chemical Company'--
'This handbook provides a framework for understanding how to characterize plastic manufacturing processes for use in troubleshooting problems. The technical level is for process engineers and production personnel'--
Includes bibliographical references and index.
Keywords: Plastics -- Molding -- Handbooks, manuals, etc; Injection molding of plastics -- Handbooks, manuals, etc